2020
DOI: 10.1159/000507257
|View full text |Cite
|
Sign up to set email alerts
|

Association between Posttransplant Opioid Use and Immunosuppressant Therapy Adherence among Renal Transplant Recipients

Abstract: Introduction: Little is known about the effect of posttransplant opioid use on adherence to immunosuppressant therapy (IST) among adult renal transplant recipients (RTRs). Objective: The aim of this study was to examine the relationship between opioid use and IST adherence among adult RTRs during the first year posttransplant. Methods: Longitudinal data were analyzed from a retrospective cohort study examining US veterans undergoing renal transplant from October 1, 2007, through March 31, 2015. Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Conversely, a single‐center analysis of 1045 kidney transplant recipients by a different study found no difference in allograft survival or patient survival but an increase in hospital readmissions among chronic opioid users 32 . Apart from survival end points, a registry trial assessing kidney transplant veterans via the US Renal Data System, Centers for Medicare and Medicaid Services Data (Medicare Part D), and Veterans Affairs pharmacy records demonstrated post‐transplant chronic opioid use was associated with significantly worse adherence to tacrolimus compared with nonopioid users 33 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, a single‐center analysis of 1045 kidney transplant recipients by a different study found no difference in allograft survival or patient survival but an increase in hospital readmissions among chronic opioid users 32 . Apart from survival end points, a registry trial assessing kidney transplant veterans via the US Renal Data System, Centers for Medicare and Medicaid Services Data (Medicare Part D), and Veterans Affairs pharmacy records demonstrated post‐transplant chronic opioid use was associated with significantly worse adherence to tacrolimus compared with nonopioid users 33 …”
Section: Resultsmentioning
confidence: 99%
“…The impact of post‐transplant opioid use on post‐transplant outcomes was described in three studies, all conducted in kidney transplant recipients 31–33 . Two assessed mortality with differing conclusions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless, like other substances, opioid use may be associated with nonadherence. For example, among middle‐aged and older adult renal transplant recipients, increased opioid use has been associated with increased nonadherence 69 …”
Section: Resultsmentioning
confidence: 99%
“…For example, among middleaged and older adult renal transplant recipients, increased opioid use has been associated with increased nonadherence. 69 It is notable that there is also a lack of findings for other commonly used substances, such as stimulants, benzodiazepines, and illicit substances in this population. These types of substances are known to be experimented with by the general population.…”
Section: Synthesis Of Findingsmentioning
confidence: 89%